Improving The User Interface of a Dealer Management System (DMS) via Design Thinking: A Case Study at Wuling Motors Indonesia - Putra, Perdana Suteja; Brilianti, Grahita Prisca; Istiqomah, Silvi; Aqidawati, Era Febriana; Afraah, Sayyidah Maulidatul (Teknoin, 2025)
PT SGMW Motor Indonesia (Wuling Motors) has used a Dealer Management System (DMS) for over five years; however, users report a cumbersome interface, non‑functional menus, and suboptimal task efficiency. This study applies a Design Thinking approach (empathize, define, ideate, prototype, test) to redesign the DMS user interface and improve user experience. We conducted interviews in the empathize stage (n=20) to build personas and journey maps, and performed formative usability testing with three user roles—dealer administrators, sales staff, and IT support—(n=9; 3 per role). Usability was evaluated using the System Usability Scale (SUS) and cognitive walkthroughs. Results show a quantitative improvement in usability (SUS: existing = XX.X, prototype = YY.Y; Δ = YY.Y − XX.X), alongside reduced steps for key tasks and clearer navigation. The study contributes a sector‑specific DMS redesign for the Indonesian automotive context and a transparent DT‑based process that other enterprise systems can replicate.